Role of Tick Commensal Bacteria in the Propagation of Emerging Infectious Diseases: Data Gaps and One Health Implications - Uday Turaga; Steven M. Presley (Zoonotic Diseases)
Ticks are obligate hematophagous ectoparasites notorious for their role as vectors of pathogens that affect humans and animals, particularly relative to the propagation of emerging infectious diseases (EIDs). Two important factors facilitating the role of ticks in the propagation of EIDs are their potential for the development of resistance to acaricides and the expansion of nonindigenous tick species into new geographic regions. The acquisition of acaricide resistance enables tick populations to be less susceptible to vector control programs. Expansion of the geographic distribution of tick populations increases the likelihood of access to new host species as well as new pathogens. Understanding of the microbiome of ticks continues to evolve, providing critical insights into tick biology. The tick microbiome largely comprises endosymbionts, pathogenic organisms, and commensal bacteria. Endosymbionts are highly preserved and vertically transmitted in ticks from mother to offspring, and their role in the survival of ticks is well recognized. Similarly, the role of ticks as vectors of pathogens is well established. However, commensal bacteria in ticks are acquired from the environment and while ingesting a blood meal. Because many tick species spend most of their lifetime off the hosts, it can be assumed that the richness and diversity of commensal bacteria are highly variable and dependent on the ecosystem in which the tick exists. This mini-review identifies some of the critical data gaps relevant to the role of and influence of commensal bacteria on the vectorial capacity of ticks. As ticks move into new habitats, are locally acquired commensal bacteria playing a role in adaptation to the new habitat? Apart from the conventionally understood mechanisms of acaricide resistance in ticks, are the commensal bacteria influencing the development of acaricide resistance at the population level?